2022
DOI: 10.1177/00111287221122753
|View full text |Cite
|
Sign up to set email alerts
|

The Bully-Victim Overlap and Vaping Activity Among Adolescents

Abstract: Previous research links substance use with bullying perpetration and bullying victimization. Limited research, however, has explored how vaping, is related to bullying activities. What limited research has been conducted links vaping with bullying victimization in some samples. However, the relationship between vaping and the victim-offender overlap is extremely limited. This study addresses this gap in the literature by exploring the associations between nicotine and marijuana vaping and bullying perpetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…Interestingly, perpetrators of bullying were three times more likely than non-perpetrators to have used an e-cigarette, while bullying victims were more likely than nonvictims to have used an e-cigarette. While these associations individually are consistent with existing literature (Azagba et al, 2020;Boccio & Leal, 2022;Doxbeck, 2020;Ihongbe et al, 2021;Liu et al, 2023;Mereish et al, 2023;Tabaac et al, 2021), it is noteworthy to examine the possible explanations for the difference in odds for perpetrators and victims. Bullying perpetrators often experience difficulties in emotional regulation, externalising behaviour and impulsivity, and are more likely to associate with delinquent peers and seek social dominance.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Interestingly, perpetrators of bullying were three times more likely than non-perpetrators to have used an e-cigarette, while bullying victims were more likely than nonvictims to have used an e-cigarette. While these associations individually are consistent with existing literature (Azagba et al, 2020;Boccio & Leal, 2022;Doxbeck, 2020;Ihongbe et al, 2021;Liu et al, 2023;Mereish et al, 2023;Tabaac et al, 2021), it is noteworthy to examine the possible explanations for the difference in odds for perpetrators and victims. Bullying perpetrators often experience difficulties in emotional regulation, externalising behaviour and impulsivity, and are more likely to associate with delinquent peers and seek social dominance.…”
Section: Discussionsupporting
confidence: 84%
“…This is the first paper to examine the relationships between peer factors and e-cigarette use in a large sample of Australian adolescents. These findings build on international research that has demonstrated associations between adolescent e-cigarette use and both perceived peer use (Barrington-Trimis et al, 2015;Cavazos-Rehg et al, 2021;Durkin et al, 2021;Patanavanich et al, 2021;Valente et al, 2023;Wang et al, 2022) and bullying involvement (Azagba et al, 2020;Boccio & Leal, 2022;Doxbeck, 2020;Ihongbe et al, 2021;Liu et al, 2023;Mereish et al, 2023;Tabaac et al, 2021). Our findings indicate that there is a robust cross-sectional association between ever using an e-cigarette and bullying perpetration, bullying victimisation, bully-victim status and perceived peer use, even after adjusting for key sociodemographic characteristics.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations